Effectiveness of team assisted individualisation-based realistic mathematics education - Widigda, Inggri Ramadhani; Mahmudi, Ali (Jurnal Riset Pendidikan Matematika, 2024)
This study aims to describe the differences in the effectiveness of the realistic mathematics education approach with team assisted individualization settings and the realistic mathematics education approach in terms of problem solving abilities and students' motivation to learn mathematics. The type of research used is quasi-experimental. The population of this study was all eighth grade students of Junior High School Negeri di Yogyakarta and two classes were taken randomly. The instruments used to collect data are problem solving test questions and a motivational questionnaire for learning mathematics. The results showed: (1) the realistic mathematics education approach with team assisted individualization settings was effective in terms of problem solving abilities and students' mathematics learning motivation, (2) the realistic mathematics education approach was effective in terms of problem solving abilities and students' mathematics learning motivation, and (3 ) there is a difference in effectiveness between the realistic mathematics education approach and the team assisted individualization setting and the realistic mathematics education approach in terms of problem solving abilities and students' motivation to learn mathematics simultaneously